ECG Abnormalities and Arterial Stiffness by HIV Status among High-Risk Populations in Rakai, Uganda: A Pilot Study - Rocio Enriquez; Robert Ssekubugu; Godfrey Kigozi; Dorean Nabukalu; Gaetano Marrone; Susanne Rautiainen; Bruna Gigante; Steven J. Reynolds; Fred Nalugoda; Larry W. Chang; Anna Mia Ekström; Nelson K. Sewankambo; et al. (Ubiquity Press, 2021)
Background: People living with HIV are at increased risk for cardiovascular disease (CVD). In sub-Saharan Africa, population-based data on major CVD events such as stroke and myocardial infarction are difficult to collect. The use of proxy measures could be a feasible way to better study CVD in such settings. This study aimed to determine the acceptance of incorporating ECG and arterial function measurements into a population-based cohort study and to assess the prevalence of ECG abnormalities and arterial stiffness. Methods: A pilot study was conducted within the Rakai Community Cohort Study in Uganda on two high-risk CVD populations; one determined by age (35-49) and Framingham CVD risk scores and the other by age alone (50+). Data on ECG, arterial function, blood pressure, and HIV status were collected. The acceptability of incorporating ECG and arterial function measurements was established as an acceptance rate difference of no more than 5% to blood pressure measurements. Results: A total of 118 participants were enrolled, 57 participants living with HIV and 61 HIV-negative participants. Both ECG measurements and arterial function were well accepted (2% difference). Left ventricular hypertrophy (LVH) and arterial stiffness (>10 m/s) were common in both participants living with HIV and HIV-negative participants across the two high-risk populations. Prevalence rates ranged from 30% to 53% for LVH and 25% to 58% for arterial stiffness. Arterial stiffness at the 11 m/s cutoff (p = 0.03) was found to be more common among participants living with HIV in the 35-49 population. Conclusions: The incorporation of ECG and arterial function measurements into routine activities of a population-based cohort was acceptable and incorporating these proxy measures into cohort studies should be explored further. LVH and arterial stiffness were both common irrespective of HIV status with arterial stiffness potentially more common among people living with HIV.